Nonlocal couple stress-based nonlinear flexural instability of laminated FG-GNRC microsize arches under arbitrary-located radial point load and unlike end supports - Sahmani, Saeid; Kotrasova, Kamila; Shahzad, Muhammad Atif; Zareichian, Mona; Safaei, Babak (Springer Wien, 2025)
This study presents a numerical investigation into the small scale-dependent nonlinear flexural instability of shallow microsize arches subjected to unlike end supports. The inhomogeneous microsize arches are constructed with a functionally graded graphene nanofiller-reinforced composite (FG-GNRC) under arbitrary-located radial point load combined with thermal conditions. In order to allow for the size dependency, the nonlocality besides the couple stress tensors is comprised within a quasi-2D parabolic shear deformable curved beam formulations. With the aid of the modified Halpin-Tsai model of micromechanics, the material characters of sandwich FG-GNRC are captured. Thenceforward, the extended isogeometric analysis is put to use embracing the insertion with the addition of multiplication of knot to manifest the necessary more depleted continuity for the coupling among the tangential and flexural reactions. It is discovered that the tensor of nonlocal stress results in to enhance the potential energies attributed to all made known condemnatory points, while it causes to decrease the correlated radial point loads. On the contrary, the tensor of couple stress plays a converse role. Withal, it is deduced that the number of condemnatory points remains unchanged after taking the consequence of temperature rise into account. What is more, as a consequence of the temperature rise, the characters of nonlocal and couple stress tensors in the quantities of radial point loads attributed to all made known condemnatory points get intense.
Keywords: Elasticity; Nanobeams; Model